Open-Ocean Convection in the Labrador and Greenland Seas: Plume Scales and Interannual Variability - Mertens, Christian (Christian-Albrechts-Universität zu Kiel, 2000)
Observations at moored stations from the Labrador and Greenland Seas are analyzed under two major aspects: the interannual variability of convection and its relation to variability of the hydrographic, meteorological, and ice conditions, and the spatial and velocity scales of individual convective plumes compared to existing scaling arguments derived from numerical and laboratory experiments. The observations were carried out in the Labrador Sea between 1994 and 1999 and in the Greenland Sea between 1988 and 1995. The convection activity observed showed considerable interannual variability throughout the observational period, but no seesaw behavior correlated with the North Atlantic Oscillation index. In the Labrador Sea, the maximum depth of convection decreased from about 1800~m in 1995 to only 600~m in 1999. The water mass properties of the winter mixed layer shifted towards warmer and less saline conditions. A general warming of the upper 2000~m was observed. Evidence for convection activity in the Labrador Sea boundary current region could not be found. The measurements were analyzed for individual events of convective plumes. During periods of intense convection activity in the Labrador Sea, it was possible to directly measure the vertical heat flux. The observed velocity scales were found to be a function of the surface buoyancy flux and the mixed layer depth and not controlled by the Earth's rotation.